Temporal orchestration of repressive chromatin modifiers by mammalian circadian clock PERIOD complexes - Duong, Hao A. (Nat Struct Mol Biol, 2014)
The mammalian circadian clock is built on a molecular feedback loop in which the PERIOD (PER) proteins, acting in a large, poorly-understood complex, repress CLOCK-BMAL1, the transcription factor driving their expression. We found that mouse PER complexes include the histone methyltransferase HP1γ-Suv39H. PER proteins recruit HP1γ-Suv39H to the Per1 and Per2 promoters, and HP1γ-Suv39H proved important for circadian di- and tri-methylation of histone-3 lysine-9 (H3K9) at the Per1 promoter, feedback transcriptional repression, and circadian clock function. HP1γ-Suv39H was recruited to the Per1 and Per2 promoters ~4 hours after HDAC1, a PER-associated protein we previously implicated in clock function and H3K9 deacetylation at the Per1 promoter. PER complexes containing HDAC1 or HP1γ-Suv39H appeared to be physically separable. Circadian clock negative feedback by the PER complex thus involves dynamic, ordered recruitment of repressive chromatin modifiers to DNA-bound CLOCK-BMAL1.